Peran Teknologi Informasi dalam Mendukung Pengambilan Keputusan - Yudistira Prayoga; Harlan Dwi Permana; Muhammad Fadzril Hijran (JUSTIFY : Jurnal Sistem Informasi Ibrahimy, 2026)
In the era of digital transformation moving at an exponential pace, data has mutated into a key strategic asset for business organizations. Speed and accuracy in managerial decision-making have become crucial determinants in maintaining competitive advantage in a volatile market. This scientific article aims to critically analyze and synthesize the role of Information Technology (IT) integration—specifically Business Intelligence (BI), Big Data Analytics, and Executive Support Systems (ESS)—in mitigating risks and improving the quality of managerial decisions. Using a descriptive-qualitative analysis approach based on a systematic literature review, this article explores how IT infrastructure intervenes in the decision-making pyramid of organizations. The analysis results show that applying data-driven IT can reduce operational uncertainty by up to 35%, improve market projection accuracy by up to 92%, and transform decision-making methodologies.